Dual-frequency on–off modulation and slow light analysis based on dual plasmon-induced transparency in terahertz patterned graphene metamaterial - Min Li; Hongjian Li; Hui Xu; Cuixiu Xiong; Mingzhuo Zhao; Chao Liu; Banxian Ruan; Baihui Zhang; Kuan Wu (New Journal of Physics, 2020)
A dual-frequency on–off modulator with considerable modulation depth (MD) and relatively low insertion loss (IL) is performed with patterned monolayer graphene metamaterial. Destructive interference in this structure gives rise to the dual plasmon-induced transparency (DPIT) phenomenon. The coupled mode theory, confirmed by simulated values, is comprehensively introduced to expound the physical mechanism of the DPIT effect. In addition, the influences of the Fermi level on the DPIT transmission spectrum and the carrier mobility of graphene on the on–off modulation are researched. It is found that the dual-frequency on–off modulator exhibits remarkable modulation performance on both switches and is easier to fabricate in operation than other multi-layer graphene-based modulators. In the ‘on _1 /off _1 ’ state, the MD and IL are 93%, 0.32 dB, respectively. In the ‘on _2 /off _2 ’ state, the MD and IL are 85%, 0.25 dB, separately. Moreover, the property of slow light reflected by the group index is analyzed. It exhibits that the group index of the proposed structure with multi-channel can reach 358. Thus, the proposed structure stretches the versatile applications in multi-function modulators and multi-channel slow light devices at the terahertz band.